2002
DOI: 10.1007/s11663-002-0042-1
|View full text |Cite
|
Sign up to set email alerts
|

Formation of CaS on Al2O3-CaO inclusions during solidification of steels

Abstract: In this article, the effect of CaS formation on the evolution of Al 2 O 3 -CaO inclusions in low-carbon Al-killed and Ca-treated steel during the solidification process is investigated through high-temperature confocal scanning laser microscopy (CSLM). The inclusions started as mostly liquid-globular inclusions that did not agglomerate with each other on the melt surface but during solidification were seen to change shape into an irregular morphology. The shape change was found to be due to the reaction betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 11 publications
0
53
0
Order By: Relevance
“…Use of high temperature CSLM, pioneered by Emi and co-workers at Tohoku University [6][7][8], and the mechanism of how it works has been documented and explained in detail in literature [5,[9][10][11][12][13][14][15]. Figure 1 shows a schematic of the set up used in this report.…”
Section: Adaption Of the Cslm To Image Using Infrared Thermographymentioning
confidence: 99%
“…Use of high temperature CSLM, pioneered by Emi and co-workers at Tohoku University [6][7][8], and the mechanism of how it works has been documented and explained in detail in literature [5,[9][10][11][12][13][14][15]. Figure 1 shows a schematic of the set up used in this report.…”
Section: Adaption Of the Cslm To Image Using Infrared Thermographymentioning
confidence: 99%
“…Wang et al 5) studied the effect of CaS formation on the evolution of Al 2 O 3 -CaO inclusions in low-carbon Al-killed steel and found that the formation of dense CaS shells around the inclusions was mainly due to the reaction between the Al 2 O 3 -CaO inclusions with the dissolved S and Al in melt. Yang et al 6) showed that calcium treatment could generate many large inclusions and the modification effect would be dramatically decreased by the formation of large amount of CaS inclusions.…”
Section: Inclusion Evolution During Modification Of Alumina Inclusionmentioning
confidence: 99%
“…Wang et al 25) investigated effect of CaS formation on the agglomerate ability of Al2O3-CaO inclusions in lowcarbon and Ca-treated steel through high-temperature confocal scanning laser microscopy (CSLM). They found liquid-globular Al2O3-CaO inclusions don't agglomerate with each other, but when CaS forms outside Al2O3-CaO, these inclusions begin to agglomerate with each other, and finally becomes clusters.…”
Section: Formation Of Cao-cas Clustersmentioning
confidence: 99%